2020
DOI: 10.15354/sief.20.or011
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of COVID-19 on the Ethiopian Education System

Abstract: The outbreak of COVID-19 at the end of 2019 lifted 2020 of the world in turmoil. Now, the world is absolutely in a unique environment. In all corners, today, the scientific world accompanies huge consequences from the novel coronavirus. The economic, social, educational, and political aspects of the world get into the abnormal conditions. This paper aimed to provide the current stance of Ethiopia's poorly equipped educational system, by focusing on the impacts of the novel Coronavirus in the provision of educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 2 publications
0
9
0
1
Order By: Relevance
“…From mid-March 2020, higher education institutions in Ethiopia closed and students’ learning was suspended, neither universities nor the ministry said anything to continue students’ learning ( Mengistie, 2020 ). The outbreak of COVID-19 is not the sole problem of Ethiopia rather it is a global problem.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From mid-March 2020, higher education institutions in Ethiopia closed and students’ learning was suspended, neither universities nor the ministry said anything to continue students’ learning ( Mengistie, 2020 ). The outbreak of COVID-19 is not the sole problem of Ethiopia rather it is a global problem.…”
Section: Resultsmentioning
confidence: 99%
“…Afew weeks after the closure, Ethiopia's government devised radio and television learning for primary and secondary levels respectively, to save the education system from the COVID-19 wave ( Mengistie, 2020 ). However, a month from the closure, students’ learning at higher education was unclear to students, parents and teachers.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the students who experienced the online learning also lamented on challenges associated with internet access. In Ethiopia, it was observed that the high cost of internet bundle served as a barrier to students accessing the e-learning platform [59]. In the case of Ghana, aside from limited ICT resources, resistance to the online modality by faculty members, and lack of social interactions, students also complained of lack of electric power supply [1].…”
Section: Online and Onsite Learning During The Pandemic Eramentioning
confidence: 99%
“…Consequently, schools were locked down for months by which students were obliged to stay at home with no education. Its effect on education is disproportionately higher in developing countries like Ethiopia due to the poor technological infrastructures that could support online education [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%